A Constructivist Analysis of the Houthi Attacks on US Merchant Ships in the Red Sea in 2023-2024 - Rifqi Nabila, Maia; Tahta Anillah, Jembar; Karimah, Hikmatul; Ubaidillah Alwani , Adhim (Faculty of Social and Political Sciences, UIN Sunan Ampel Surabaya, 2025)
The Houthi attacks on United States commercial vessels in the Red Sea during 2023–2024 have drawn global attention to maritime security dynamics and regional conflicts. This study aims to analyze the ideas, identities, and narratives that shape Houthi actions through the lens of constructivism in international relations. Employing a qualitative approach and in-depth case study, data were collected through semi-structured interviews with global security experts and content analysis of official Houthi statements and international media coverage. Findings indicate that Houthi actions are not solely driven by military objectives but are also motivated by ideas of solidarity with Gaza, the collective identity of the Arab world, and a Global South resistance against Western hegemony. Furthermore, Shia ideology reinforces the alliance with Iran as Houthi’s primary backer, with suspicions of major power involvement such as China within a proxy war context. Houthi narratives frame the attacks as a moral and political struggle against global injustice, resonating broadly across the region. The study underscores the importance of ideational and identity dimensions in understanding contemporary conflict dynamics and recommends strengthening narrative analysis in international security studies.